Effect of Lactic Acid Filtrate and Bacteriocins of Lactobacillus acidophillus on Phagocytosis Activity of Macrophages Cell againts Enteropathogen Escherichia coli (EPEC) - IIS HERAWATI; DIKI HILMI; PRIMA NANDA FAUZIAH (Indonesian Society for microbiology, 2014)
Immunity development known as one of effective ways in avoiding infection. Antibacterial agent product isolated from Lactobacillus acidophillus has been Â reported can activate T lymphocyte as part of adaptive immunity. This experimental study aimed at investigation of lactic acid and bacteriocins filtrate from L. acidophillus in modulating phagocytosis activity of human macrophages infected by enteropathogenic Escherichia coli (EPEC). Each of human macrophages culture was supplemented with lactic acid and bacteriocins filtrate at concentration of 3.125, 6.25, and 12.5 Âµg mL-1 as well as control without filtrate addition and incubated for 24 h. Macrophages culture was then infected with EPEC for 30 minutes and was microscopically observed after being stained by Giemsa. Percentage of phagocytosis activity was gained from active macrophages in 100 observed cells. Macrophages cultures supplemented with bacteriocins filtrate showed augmented phagocytosis activity while cultures supplemented with lactic acid filtrate showed decreased phagocytosis activity. ANOVA analysis showed significant difference in phagocytosis activity of macrophage cultures supplemented with lactic acid (p=0,038) and bacteriocins (p=0,016 and 0,023). Tukey HSD analysis for phagocytosis activity of macrophage cultures supplemented by bacteriocins, each group of treatment showed significant difference againts control. In conclusion, lactic acid from Â L.acidophillus has no effect in modulation of macrophages phagocytosis activity while bacteriocins can improve phagocytic activity. Bacteriocins from L. acidophillus then can be suggested to have a role as immunomodulator.